Australian Aboriginal children have higher hospitalization rates for otitis media but lower surgical procedures than non-Aboriginal children: A record linkage population-based cohort study. - Darren W Westphal; Deborah Lehmann; Stephanie A Williams; Peter C Richmond; Francis J Lannigan; Parveen Fathima; Christopher C Blyth; Hannah C Moore (PLoS ONE)
Introduction Otitis media (OM) is one of the most common infectious diseases affecting children globally and the most common reason for antibiotic prescription and paediatric surgery. Australian Aboriginal children have higher rates of OM than non-Aboriginal children; however, there are no data comparing OM hospitalization rates between them at the population level. We report temporal trends for OM hospitalizations and in-hospital tympanostomy tube insertion (TTI) in a cohort of 469,589 Western Australian children born between 1996 and 2012. Materials and methods We used the International Classification of Diseases codes version 10 to identify hospitalizations for OM or TTI recorded as a surgical procedure. Using age-specific population denominators, we calculated hospitalization rates per 1,000 child-years by age, year and level of socio-economic deprivation. Results There were 534,674 hospitalizations among 221,588 children hospitalized at least once before age 15 years. Aboriginal children had higher hospitalization rates for OM than non-Aboriginal children (23.3/1,000 [95% Confidence Interval (CI) 22.8,24.0] vs 2.4/1,000 [95% CI 2.3,2.4] child-years) with no change in disparity over time. Conversely non-Aboriginal children had higher rates of TTI than Aboriginal children (13.5 [95% CI 13.2,13.8] vs 10.1 [95% CI 8.9,11.4]). Children from lower socio-economic backgrounds had higher OM hospitalization rates than those from higher socio-economic backgrounds, although for Aboriginal children hospitalization rates were not statistically different across all levels of socio-economic disadvantage. Hospitalizations for TTI among non-Aboriginal children were more common among those from higher socio-economic backgrounds. This was also true for Aboriginal children; however, the difference was not statistically significant. There was a decline in OM hospitalization rates between 1998 and 2005 and remained stable thereafter. Conclusion Aboriginal children and children from lower socio-economic backgrounds were over-represented with OM-related hospitalizations but had fewer TTIs. Despite a decrease in OM and TTI hospitalization rates during the first half of the study for all groups, the disparity between Aboriginal and non-Aboriginal children and between those of differing socioeconomic deprivation remained.